Description of the first two tropical Indo-Pacific species of Dendronotus (Gastropoda: Nudibranchia) with new data of the poorly known species Dendronotus gracilis Baba, 1949 - Pola, Marta; Stout, Carla C. (Zootaxa, 2008)
Dendronotus regius sp. nov. and Dendronotus noahi sp. nov. are the first two species of the genus Dendronotus Alder & Hancock described from tropical western Pacific waters. Both have unique color patterns as well as radulae that are distinct from other known species of the genus. Dendronotus regius sp. nov. is recorded from Indonesia, the Philippines and Malaysia while Dendronotus noahi sp. nov. is found in Papua New Guinea. Along with these descriptions, new data on D. gracilis Baba, 1949 are given to provide supplemental information on its morphology and report an increase in its range to include the tropical waters of Okinawa, Japan. A comparative table as well as scanning electron micrographs for almost all recognized species is also provided.